Validitas Modul Pembelajaran Biologi Materi Jaringan Pada Tumbuhan Kelas XI. IPA MAN 1 Solok Selatan - Azhari, Novia; Fitriani, Vivi; Safitri, Elza (Jurnal Pendidikan, Sains Dan Teknologi, 2024)
A module is a type of teaching material that is packaged completely and systematically. MAN 1 Solok Selatan already has teaching materials, namely textbooks. In terms of the availability of textbooks at the school, it is not sufficient for the number of students, so not all students can borrow textbooks. There are shortcomings in the package book, namely that the material in the book is still minimal, as well as a lack of pictures of plant tissue. This research aims to produce a module on tissue material in plants for class XI. IPA MAN 1 Solok Selatan which is very valid and very practical. This research was conducted in the odd semester of the 2023/2024 academic year in class XI. IPA at MAN 1 Solok Selatan. This research is development research using a 4-D model which includes 4 stages, namely the define, design, develop and disseminate stages. This research was only carried out at the develop stage, namely validity testing. In the define stage, front end analysis is carried out (using questionnaires and interviews), student analysis, and task analysis starting from content structure analysis, concept analysis and learning objective analysis. The design stage is carried out by designing modules. In the develop stage, a validity test was carried out by filling out a questionnaire by 2 lecturers and 1 Biology teacher. Data were analyzed using percentage techniques and processed using descriptive analysis. The validity results by lecturers and teachers obtained an average of 91.81% with very valid criteria. It can be concluded that the module on plant tissue material for class XI IPA MAN 1 South Solok that was developed is very valid.